Balancing selection and genetic drift create unusual patterns of MHCIIβ variation in Galápagos mockingbirds - Vlček, Jakub; Hoeck, Paquita E A; Keller, Lukas F; Wayhart, Jessica P; Dolinová, Iva; Štefka, Jan (Molecular ecology, 2016)
The extracellular subunit of the major histocompatibility complex MHCIIβ plays an important role in the recognition of pathogens and the initiation of the adaptive immune response of vertebrates. It is widely accepted that pathogen-mediated selection in combination with neutral micro-evolutionary forces (e.g. genetic drift) shape the diversity of MHCIIβ, but it has proved difficult to determine the relative effects of these forces. We evaluated the effect of genetic drift and balancing selection on MHCIIβ diversity in 12 small populations of Galápagos mockingbirds belonging to four different species, and one larger population of the Northern mockingbird from the continental USA. After genotyping MHCIIβ loci by high-throughput sequencing, we applied a correlational approach to explore the relationships between MHCIIβ diversity and population size by proxy of island size. As expected when drift predominates, we found a positive effect of population size on the number of MHCIIβ alleles present in a population. However, the number of MHCIIβ alleles per individual and number of supertypes were not correlated with population size. This discrepancy points to an interesting feature of MHCIIβ diversity dynamics: some levels of diversity might be shaped by genetic drift while others are independent and possibly maintained by balancing selection.
Keywords: Genetic Variation; Genetics, Population; Population Density; zvířata; populační genetika; Passeriformes; ostrovy; Genes, MHC Class II; Animals; genetická variace; Ecuador; Genotype; Ekvádor; hustota populace; geny MHC třídy II; Genetic Drift; genetický drift; genotyp; selekce (genetika); Islands; Selection, Genetic